Association study of GRM7 polymorphisms and schizophrenia in the Chinese Han population. (14th September 2015) - Niu, Weibo; Huang, Xiaoye; Yu, Tao; Chen, Shiqing; Li, Xingwang; Wu, Xi; Cao, Yanfei; Zhang, Rui; Bi, Yan; Yang, Fengping; Wang, Lu; Li, Weidong; et al.
Highlights: We investigated the association between the GRM7 gene and schizophrenia. The two SNPs demonstrated significant difference between patients and controls. The GRM7 might be associated with schizophrenia in Chinese Han population. Abstract: Schizophrenia is a severe and complex mental disorder with high heritability. There is an evidence that metabotropic glutamate receptors (GRM) are associated with schizophrenia. GRM7 has been identified as a candidate gene for many psychiatric disorders especially schizophrenia. In this study, we investigated whether single nucleotide polymorphisms (SNPs) in GRM7 were associated with schizophrenia. Four SNPs (rs9814881, rs13353402, rs9870680 and rs1531939) were genotyped in 1034 schizophrenic patients and 1034 healthy controls of Chinese Han origin. The results showed that the two SNPs rs13353402 and rs1531939 demonstrated significant difference between schizophrenic patients and control subjects in allele frequencies (rs13353402: P value = 0.0307, rs1531939: P value = 0.0328, respectively). Nevertheless, there was no significant discrepancies in genotype distribution. In summary, our results indicate that the GRM7 SNPs rs13353402 and rs1531939 might be associated with schizophrenia in Chinese Han population.